Answer:
[tex]y = 4a - 5[/tex]
Step-by-step explanation:
Let y represent the given situation.
Given:
Andrew's age = a
We need to find the expression for given abatement.
Solution:
The given statement: Five years less than four times Andrew’s age
Five years less than four times Andrew’s age = [tex]4\times (Andrew's\ age) - 5[/tex]
Andrew's age is known, so we substitute Andrew's age = a
[tex]y = 4\times (a) - 5[/tex]
[tex]y = 4a - 5[/tex]
Therefore, the expression for the given situation [tex]y = 4a - 5[/tex]